Regulators of complement activity mediate inhibitory mechanisms through a common C3b‐binding mode. (24th March 2016) - Forneris, Federico; Wu, Jin; Xue, Xiaoguang; Ricklin, Daniel; Lin, Zhuoer; Sfyroera, Georgia; Tzekou, Apostolia; Volokhina, Elena; Granneman, Joke CM; Hauhart, Richard; Bertram, Paula; Liszewski, M Kathryn; et al.
Abstract: Regulators of complement activation (RCA) inhibit complement‐induced immune responses on healthy host tissues. We present crystal structures of human RCA (MCP, DAF, and CR1) and a smallpox virus homolog (SPICE) bound to complement component C3b. Our structural data reveal that up to four consecutive homologous CCP domains (i–iv), responsible for inhibition, bind in the same orientation and extended arrangement at a shared binding platform on C3b. Large sequence variations in CCP domains explain the diverse C3b‐binding patterns, with limited or no contribution of some individual domains, while all regulators show extensive contacts with C3b for the domains at the third site. A variation of 100° rotation around the longitudinal axis is observed for domains binding at the fourth site on C3b, without affecting the overall binding mode. The data suggest a common evolutionary origin for both inhibitory mechanisms, called decay acceleration and cofactor activity, with variable C3b binding through domains at sites ii, iii, and iv, and provide a framework for understanding RCA disease‐related mutations and immune evasion. Synopsis: Complement activity is controlled by regulators binding to C3b or C4b. Analysis of five C3b regulator structures reveals that both decay‐acceleration and cofactor activity depend on a common C3b‐regulator binding mode. Crystal structures reveal C3b binding of four human and viral complement regulators Common mode of C3b binding underlies decay‐acceleration and cofactor activity Extensive variations in interaction details explain diverse characteristics of regulators C3b‐regulator structures provide basis for understanding disease‐related mutations Abstract : Structural insights into how complement factor C3b binds to human and viral regulators of complement activation aid our understanding of disease‐related mutations and SNPs affecting complement control.